Whole blood RNA signatures in tuberculosis patients receiving H56:IC31 vaccine as adjunctive therapy - Alonso-Rodríguez, Noelia; Vianello, Eleonora; van Veen, Suzanne; Jenum, Synne; Tonby, Kristian; van Riessen, Rosalie; Lai, Xiaoran; Mortensen, Rasmus; Ottenhoff, Tom H. M.; Dyrhol-Riise, Anne Ma (Frontiers in Immunology, 2024)
Therapeutic vaccination in tuberculosis (TB) represents a Host Directed Therapy strategy which enhance immune response in order to improve clinical outcomes and shorten TB treatment. Previously, we have shown that the subunit H56:IC31 vaccine induced both humoral and cellular immune responses when administered to TB patients adjunctive to standard TB treatment. Here we present the longitudinal whole blood gene expression patterns in H56:IC31 vaccinated TB patients compared to controls receiving standard TB treatment only. A targeted gene expression profiling platform on 183 immune-and TB-related genes unveiled the upregulation of modules such as interferon (IFN) signalling genes, pattern recognition receptors and small nucleotide guanosine triphosphate (GTP)-ases in the vaccinated group compared to controls two weeks after administration of the first H56:IC31 vaccine.Additionally, the longitudinal analysis of the Adolescent Cohort Study-Correlation of Risk (ACS-COR) signature showed a progressive downregulation in both study arms towards the end of TB treatment, in congruence with reported treatment responses and clinical improvements. Still, two months after the end of TB treatment, vaccinated patients, and especially those developing both cellular and humoral vaccine responses, showed a lower expression of the ACS-COR genes compared to controls, which might be interpreted as a lower risk of relapse in therapeutically vaccinated subjects. Our data report gene expression patterns following H56:IC31 vaccination that would benefit from further exploration to conclude if they could be used as therapeutic biosignatures for TB vaccine responses.